2013
DOI: 10.1186/1471-2334-13-158
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-guided algorithm to reduce length of antibiotic therapy in patients with severe sepsis and septic shock

Abstract: BackgroundProcalcitonin (PCT)-protocols to guide antibiotic treatment in severe infections are known to be effective. But less is known about the long-term effects of such protocols on antibiotic consumption under real life conditions. This retrospective study analyses the effects on antibiotic use in patients with severe sepsis and septic shock after implementation of a PCT-protocol.MethodsWe conducted a retrospective ICU-database search for adult patients between 2005 and 2009 with sepsis and organ dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 39 publications
(50 reference statements)
2
50
0
6
Order By: Relevance
“…-Procalcitonin has been proposed as a marker of infection [60][61][62][63]. Furthermore, it may be useful as an indicator of the severity of infection and as a guide for therapy (dose de-escalation [64]) in respiratory infections [61,62,[65][66][67][68].…”
Section: The Diagnosis Of Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…-Procalcitonin has been proposed as a marker of infection [60][61][62][63]. Furthermore, it may be useful as an indicator of the severity of infection and as a guide for therapy (dose de-escalation [64]) in respiratory infections [61,62,[65][66][67][68].…”
Section: The Diagnosis Of Sepsismentioning
confidence: 99%
“…The use of procalcitonin [64,144,145] or similar biomarkers may facilitate discontinuance of antibiotics in a patient with clinical improvement, although one recent study failed to show any benefit of daily procalcitonin measurement [146]. Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93].…”
Section: The Empirical Treatment Must Be Optimized When Microbiology mentioning
confidence: 99%
“…Various clinical cutoffs for PCT are established for various clinical settings, with higher cutoffs being used in critical care and sepsis and lower cutoffs being used in immunocompromised patients, or to guide antibiotic decisions [4]. PCT-based clinical algorithms have been proposed to guide antibiotic therapy both for patients with lower respiratory tract infections (LRTI), including pneumonia, acute exacerbations of chronic obstructive pulmonary disease and acute bronchitis as well as for critically ill patients [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of a series of PCT levels has consistently been described as useful for the evaluation of therapeutic success [7,21]. Hohn et al demonstrated these effects, even among routine clinical populations [22]. In addition, numerous clinical studies have confirmed that antibiotic therapy can be stopped when PCT levels have normalized and clinical improvement has occurred, without risk of increased mortality.…”
Section: Discussionmentioning
confidence: 89%